Ockham's razor is not so sharp - Mark Lewis; Kartik Agusala; Yuval Raizen (MDPI AG, 2010)
A 39-year-old male with newly diagnosed HIV had cavitary pneumonia initially attributed to Pneumocystis jirovecii but actually caused by Rhodococcus equi. After neurological deterioration, he was found to have intracerebral lesions caused by Toxoplasma gondii. This case underscores the inability to rely on the search for a unifying diagnosis (Ockham's Razor) in HIV-infected patients.